SITUATING WOMEN IN SOCIETY: A STUDY ON TRADITIONAL MANTRAS OF BANJAR - Ninuk Krismanti (Universitas Putera Batam, 2020)
The glory of traditional mantras of Banjar may have passed; however, mantras are still valuable products of traditional literatures of Banjarese society. This study was conducted to describe social treatments for women in the given society as reflected in traditional mantras. The data of the study were 35 love and conquering mantras extracted from four books. The data were collected through documentation technique. The data were analyzed using Antropholinguistics approach with two focuses of analyses: functions and contents. From functions and contents of mantras, the researcher interpreted the results of the study. After analyzing the data, the researcher concluded that women were still inferior compared to men. Women were the ones working harder to keep their position and relationship with men safe. Furthermore, their position in the society was sub-ordinate because the main roles given to them were domestic roles.